Local release of gemcitabine via in situ UV-crosslinked lipid-strengthened hydrogel for inhibiting osteosarcoma. (1st January 2018) - Wu, Wei; Dai, Yong; Liu, Han; Cheng, Ruoyu; Ni, Qing; Ye, Tingjun; Cui, Wenguo
Abstract: Osteosarcoma is among the most common malignant bone tumors in human skeletal system. The conventional treatment of osteosarcoma mainly consists of combining neoadjuvant chemotherapy with surgical approach. However, it is crucial to design an artificial implant that possesses excellent biomechanical properties and is capable of sustaining local release of chemotherapeutics. In this study, we envision that the highly efficient combination of gemcitabine (GEM) hydrochloride loaded liposomes with gelatin methacryloyl (GelMA) of in situ photocrosslinkable hydrogel will lead to a multifunctional implant with unique antitumor, mechanical, and biodegradable properties. A sustained controlled release was observed; more specifically, the release of GEM in vitro lasted for 4 days long. Furthermore, its capability in killing MG63 cells was further explored by using the lixivium of GEM-Lip@Gel and GEM-GelMA hydrogel in vitro (composite hydrogel by GEM loaded liposomes blending with GelMA, short for GEM-Lip@Gel), which agreed with the drug release outcome. In addition, these hydrogel showed excellent ability in inhibiting osteosarcoma in vivo by Balb/c mice bearing MG63 cells. Therefore, GEM-loaded lipo-hydrogel certainly has presented itself as a promising strategy for the development of implant in the field of osteosarcoma treatment. Graphical Abstract: